ANGI-1 ASSESSING THE THERAPEUTIC EFFECT OF BEVACIZUMAB USING FMISO-PET IN GBM THERAPY. (3rd December 2022) - Suzuki, Tomoya; Tanaka, Toshihide; Takei, Jun; Miyake, Keisuke; Suzuki, Kenta; Ogawa, Daisuke; Akasaki, Yasuharu; Yuichi, Murayama
Abstract: Background: Gd-enhanced MRI and T2WI/FLAIR images are used to determine the efficacy of bevacizumab(Bev) in glioblastoma(GBM). FMISO-PET reflects hypoxia in tumor tissue. In this study, we hypothesized that FMISO-PET could detect a series of changes in the hypoxic environment during the Bev effect and at the time of Bev recurrence, and compared images and pathological findings after initial Bev treatment and recurrence. Subjects and Methods: Seven patients with first-episode GBM, IDH-wild type were included in the study. 3 patients underwent tumor resection after completion of Bev, radiation, and temozolomide treatment, and reoperation was performed at recurrence. FMISO-PET was performed at each time point. Four patients who underwent tumor resection after FMISO-PET in the absence of treatment were also included. The explanted specimens were analyzed for expression of hypoxia (CA9) and stem cell surface marker (FOXM1) by immunohistochemistry (IHC). Results: All three patients treated with preoperative chemoradiotherapy showed reduced FMISO accumulation. Two of them showed recurrence and increased FMISO accumulation, and IHC showed increased CA9 and FOXM1 positive cells at the time of reoperation. There was a trend toward fewer CA9-positive cells in patients with low FMISO accumulation, including controls. Conclusion: FMISO-PET was used to visualize the improvement of oxygenation in tumor tissues after preoperative chemoradiotherapy including Bev, and the increased FMISO accumulation at the time of Bev resistance suggested that FMISO-PET may be useful for monitoring the duration of Bev treatment effect by reflecting the oxygenation of tumor tissues. The results suggest that FMISO-PET may be useful for monitoring the duration of response to Bev therapy.